ChemInform Abstract: Green and Rapid Access to Benzocoumarins via Direct Benzene Construction Through Base‐Mediated Formal [4 + 2] Reaction and Air Oxidation. Issue 28 (June 2016) - Mou, Chengli; Zhu, Tingshun; Zheng, Pengcheng; Yang, Song; Song, Bao‐An; Chi, Yonggui Robin
Abstract: The title procedure can be successfully applied to the construction of a broad spectrum of benzocoumarin derivatives starting from 3‐acetylcoumarins and unsaturated aldehydes (loss of acetic acid).